Insulin resistance, metabolic syndrome and polycystic ovaries: an intriguing conundrum - Prosperi, Sara; Chiarelli, Francesco (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a multisystemic disorder and occurs as the most common endocrine condition in adolescent girls and young women. There is a strict interplay between PCOS and insulin resistance, obesity, and features of the metabolic syndrome; the link between these conditions is complex and often bidirectional: insulin resistance exacerbates hyperandrogenism and ovulatory dysfunction, and PCOS itself increases the risk of developing impaired glucose tolerance and type 2 diabetes mellitus (T2D). As the diagnosis of PCOS is mostly clinical, physicians need to be aware of the fact that, during adolescence, physiological insulin resistance of puberty and menstrual irregularity in the first years post menarche can complicate the diagnostic process, leading to both over- and under-diagnosis of PCOS. This review article explores the central role of insulin resistance as a unifying mechanism underlying both metabolic and reproductive dysfunction in young women, highlighting the overlapping clinical features, the difficulties in applying adult-based diagnostic criteria to adolescents, and the importance of identifying early red flags. Management requires a multidisciplinary approach that prioritizes lifestyle modification, psychological support, and, where needed, pharmacological interventions. Early recognition is critical to prevent long-term complications, including infertility, endometrial hyperplasia, and cardiovascular disease. Given the rising prevalence of insulin resistance, T2D and PCOS in youth, clinicians must become increasingly familiar with this metabolic and endocrine challenge in order to implement timely individualized care.